"For the benefit of all students": Student trust in higher education learning analytics practices. Issue 1 (18th October 2019) - Jones, Kyle M. L.; Afnan, Tanisha
ABSTRACT: Learning analytics is a sociotechnical practice that seeks new insights from mining and analyzing student data. As new flows of student data emerge and granular information about student life becomes more accessible, there is a growing call to address student privacy and related issues. This poster reports emerging results from over 100 interviews with undergraduate students regarding their privacy perceptions especially with regard to trust.